Chronic Lung Allograft Dysfunction: Evolving Concepts and Therapies - Amubieya, Olawale; Ramsey, Allison; DerHovanessian, Ariss; Fishbein, Gregory A.; Lynch, Joseph P., III; Belperio, John A.; Weigt, S. Samuel (Seminars in Respiratory and Critical Care Medicine, 2021)
The primary factor that limits long-term survival after lung transplantation is chronic lung allograft dysfunction (CLAD). CLAD also impairs quality of life and increases the costs of medical care. Our understanding of CLAD continues to evolve. Consensus definitions of CLAD and the major CLAD phenotypes were recently updated and clarified, but it remains to be seen whether the current definitions will lead to advances in management or impact care. Understanding the potential differences in pathogenesis for each CLAD phenotype may lead to novel therapeutic strategies, including precision medicine. Recognition of CLAD risk factors may lead to earlier interventions to mitigate risk, or to avoid risk factors all together, to prevent the development of CLAD. Unfortunately, currently available therapies for CLAD are usually not effective. However, novel therapeutics aimed at both prevention and treatment are currently under investigation. We provide an overview of the updates to CLAD-related terminology, clinical phenotypes and their diagnosis, natural history, pathogenesis, and potential strategies to treat and prevent CLAD.
Keywords: lung transplantation; chronic rejection; chronic lung allograft dysfunction; bronchiolitis obliterans syndrome; restrictive allograft syndrome